The Relationship between Emotional Intelligence and Psychological Well-Being among Male University Students: The Mediating Role of Perceived Social Support and Perceived Stress - Romualdas Malinauskas (International Journal of Environmental Research and Public Health, 2020)
This study aimed to examine the subject of emotional intelligence (EI), which has received increased attention from scholars over the past few decades. The study utilized a quantitative longitudinal approach to attain the objective of understanding the correlation between EI and psychological well-being. A sample consisting of only male students was sought in this study in a process that was guided by specific criteria. The study reveals that students’ EI correlates positively with perceived social support and well-being at each time and across times. Negative relations are found between perceived stress and well-being at each time and across times. Results and findings reported in this study reveal that perceived social support partially mediates the longitudinal association between EI and well-being. Specifically, perceived stress does not mediate the longitudinal association between EI and well-being.